2004
DOI: 10.2337/diacare.27.12.2824
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Preterm Delivery in Women With Type 1 Diabetes

Abstract: OBJECTIVE -The reported rate of preterm delivery in women with type 1 diabetes ranges from 22 to 45%, but the reasons are unclear. The purpose of this study was to identify factors associated with preterm delivery in these women. RESEARCH DESIGN AND METHODS-We studied the influence of maternal and diabetes-related factors on the occurrence of preterm delivery in 168 single pregnancies occurring in 127 women with type 1 diabetes. Women with spontaneous or indicated preterm delivery were compared with those who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 22 publications
5
47
3
4
Order By: Relevance
“…Our data show a highly statistically significant association between prepregnancy care and very premature delivery and suggest that not having received prepregnancy care was an important predictor of very premature delivery, even after correction for potential confounding factors including smoking status. A recent French study of premature delivery in women with type 1 diabetes suggested that the risk of premature delivery was related to glycemic control around the time of delivery (25). In contrast, our results suggest that early glycemic control is also important as the benefits of prepregnancy care on glycemic control were greatest in early pregnancy.…”
Section: Statistical Analysescontrasting
confidence: 76%
“…Our data show a highly statistically significant association between prepregnancy care and very premature delivery and suggest that not having received prepregnancy care was an important predictor of very premature delivery, even after correction for potential confounding factors including smoking status. A recent French study of premature delivery in women with type 1 diabetes suggested that the risk of premature delivery was related to glycemic control around the time of delivery (25). In contrast, our results suggest that early glycemic control is also important as the benefits of prepregnancy care on glycemic control were greatest in early pregnancy.…”
Section: Statistical Analysescontrasting
confidence: 76%
“…On the other hand, even though almost 80% of patients in 2000-2011 had their HbA 1c controlled within 12 months before pregnancy, early pregnancy glycaemic control did not improve. Poor glycaemic control increases the risk of congenital malformations [30,31], preterm delivery [32] and pre-eclampsia [33], all of which were common in our study. The rate of fetal malformations was close to the levels reported 30 years ago [5,8].…”
Section: Discussionmentioning
confidence: 56%
“…21,22 Both poor glycemic control and hypertension have previously been associated with preterm delivery among women with type 1 diabetes. [23][24][25][26] Nearly 60% of the women with IBP had hypertension, a majority of whom had chronic hypertension. The increased malformations in this group in the subset of infants with follow-up data may be reflective of poor glycemic control.…”
Section: Figurementioning
confidence: 99%